Activation of the AMPK-SIRT1 pathway contributes to protective effects of Salvianolic acid A against lipotoxicity in hepatocytes and NAFLD in mice - Li, Songtao; Qian, Qianyu; Ying, Na; Lai, Jianfei; Feng, Luyan; Zheng, Sitong; Jiang, Fusheng; Song, Qing; Chai, Hui; Dou, Xiaobing (Frontiers in Pharmacology, 2020)
Background: Salvianolic acid A (Sal A), a natural polyphenol compound extracted from Radix Salvia miltiorrhiza (known as Danshen in China), possesses a variety of potential pharmacological activities. The aim of this study is to determine mechanisms of hepatoprotective effects of Sal A against lipotoxicity both in cultured hepatocytes and in a mouse model of fatty liver disease. Methods: High-fat/high-carbohydrate diet (HFCD)-fed C57BL/6J mice were employed to establish hepatic lipotoxicity in a mouse model. Two doses of Sal A were administered every other day via intraperitoneal injection (20 and 40 mg/kg BW, respectively). After a 10-week intervention, liver injury was detected by immunohistochemical and biochemical analyses. For in vitro studies, we used HepG2, a human hepatoma cell line, and exposed them to palmitic acid to induce lipotoxicity. The protective effects of Sal A on palmitic acid-induced lipotoxicity were examined in Sal A-pretreated HepG2 cells. Results: Sal A treatments attenuated body weight gain, liver injury, and hepatic steatosis in mice exposed to HFCD. Sal A pretreatments ameliorated palmitic acid-induced cell death, but did not reverse effects of HFCD- or palmitate-induced activations of JNK, ERK1/2, and PKA. Induction of p38 phosphorylation was significantly reversed by Sal A in HFCD-fed mice, but not in palmitate-treated HepG2 cells. However, Sal A rescued hepatic AMP-activated protein kinase (AMPK) suppression and sirtuin 1 (SIRT1) downregulation by both HFCD feeding in mice and exposure to palmitate in HepG2 cells. Sal A dose-dependently up-regulated p-AMPK and SIRT1 protein levels. Importantly, siRNA silencing of either AMPK or SIRT1 gene expression abolished the protective effects of Sal A on lipotoxicity. Moreover, while AMPK silencing blocked Sal A-induced SIRT1, silencing of SIRT1 had no effect on Sal A-triggered AMPK activation, suggesting SIRT1 upregulation by Sal A is mediated by AMPK activation. Conclusion: Our data uncover a novel mechanism for hepatoprotective effects of Sal A against lipotoxicity both in livers from HFCD-fed mice and palmitic acid-treated hepatocytes.